Emotional Analysis of Karate Athletes When Competing in Kumite Number - Sonjaya, Azhar Ramadhana; Ma'mun, Amung; Kusmaedi, Nurlan; Juliantine, Tite; Setiawan, Muhamad Rizal (Universitas Majalengka, 2024)
This paper aims to show the factors that influence karate athletes in the kumite category when competing and provide an overview of how to control emotions by karate athletes in the kumite category when competing. This paper uses a descriptive method with a non-experimental design. The population in this paper is karate athletes in the kumite category in Garut Regency, totaling 57 people. The sampling technique used is purposive sampling, so that the total sample in this paper is 17 people. Data collection in this study used observation, questionnaires and interviews. The results of this study indicate that there is an influence of emotions in the form of internal factors of 82.07% (high category) on athletes when competing, in addition to internal factors there is also an influence of external factors of 17.92% (moderate category) on karate athletes when competing in the kumite category. Recognizing the emotions that will arise when competing is a way for athletes to control their emotions when competing.